2020
DOI: 10.1177/0894845320946399
|View full text |Cite
|
Sign up to set email alerts
|

Career Mentoring and Job Content Plateaus: The Roles of Perceived Organizational Support and Emotional Exhaustion

Abstract: The study aims to shed light on whether mentoring may help protégés decrease their perception of job content plateaus. Based on the conservation of resources theory, career mentoring could be an effective resource in decreasing job content plateaus and alleviating the resulting emotional exhaustion. The study also proposes that perceived organizational support (POS) can be an organizational resource for protégés, strengthening the effects of career mentoring in addressing the problem of job content plateaus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…This may be due to around quarter of nursing staff had postgraduate studies and high percent of them agreed that they seek to increase their knowledge, invest in relationship, and build a network, and adhere to workplace policy of performance. These results were supported by Kao et al (2022) (10) , Shabeer et al (2019) (3) , and Mariano et al (2016) (33) they revealed that setting scientific conferences and educational programs allow nursing staff to refresh and increase their knowledge that would put them in the priority of advancement opportunity and reduce feeling of stress.…”
Section: Levels Of Nursing Staff Management Strategies Of Career Plateaumentioning
confidence: 70%
See 2 more Smart Citations
“…This may be due to around quarter of nursing staff had postgraduate studies and high percent of them agreed that they seek to increase their knowledge, invest in relationship, and build a network, and adhere to workplace policy of performance. These results were supported by Kao et al (2022) (10) , Shabeer et al (2019) (3) , and Mariano et al (2016) (33) they revealed that setting scientific conferences and educational programs allow nursing staff to refresh and increase their knowledge that would put them in the priority of advancement opportunity and reduce feeling of stress.…”
Section: Levels Of Nursing Staff Management Strategies Of Career Plateaumentioning
confidence: 70%
“…Strategies Structure Questionnaire. It was developed by the researcher guided by Nwabueze (2016) (14) and Shakila & Basariya (2019) (10) . It used to assess career plateau management strategies and consisted of (21 items) included 3 subscales, defense strategy (7 items), reevaluation strategy (7 items), and transition strategy (7 items).…”
Section: Part (3): Carrer Plateau Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Promotion or promotion is an opportunity for advancement in the organization (Kao et al, 2022) argue that promotion is a career defined as a sequence of separate but related work activities that provide continuity and meaning in one's life. When someone is promoted, it shows that someone has good work performance which is accompanied by an increase in responsibility and social status.…”
Section: A the Effect Of Employee Satisfaction On Job Involvementmentioning
confidence: 99%
“…Scholars have found that perceived organizational support (POS), as a situational characteristic, can subtly influence employees’ behaviors beneficial to the organization (DeConinck, 2010 ; Lam et al, 2016 ). When POS level is high, employees can obtain more resources from the organization, which can relieve their consumption of emotional resources to a certain extent (Chen & Eyoun, 2021 ; Kao et al, 2020 ), and ultimately affect their cognitive units and behaviors (Mischel & Shoda, 1995 ; Yao et al, 2020 ). Thus, we propose that POS moderates the chain-mediating model linking W_ICTs to time theft via the chain-mediators of emotional exhaustion and moral disengagement.…”
Section: Introductionmentioning
confidence: 99%